Theoretical aspects of the process of technical magnetization of rare earth terbium ferrite garnet in the temperature range of magnetic compensation - Sharipov Mirzo; Hayitov Dilshod; Ergasheva Nilufar; Zokirova Zarkhal; Fayzieva Zarifa (EPJ Web of Conferences)
The article presents an interpretation of the results obtained from studies of the process of technical magnetization of terbium ferrite garnet near the magnetic compensation temperature point, which were carried out within the framework of the thermodynamic theory of domain structures. The model used for changing the domain position of a rare-earth magnet with changes in the magnetic field and temperature makes it possible to qualitatively describe the identified patterns of the process of technical magnetization of ferrite garnet during a transition near the temperature of magnetic compensation.